'This is my garden': justice claims and struggles over forests in Vietnam's REDD+. (22nd July 2019) - Hoang, Cam; Satyal, Poshendra; Corbera, Esteve
ABSTRACT: This paper explores dynamics of conflict over forests in Vietnam, as the country lays the groundwork for Reducing Emissions from Deforestation and Forest Degradation (REDD+). Drawing on a case study in Lam Dong province and applying an environmental justice lens, we examine how various social actors assert claims over forests and how these claims invoke different notions of justice, authority and identity. Our analysis highlights that the development and implementation of the project has generated renewed competing claims and conflicts over forests among social actors. Underlying these conflicts there are incompatible notions of justice and associated rights, which lead different actors to accord legitimacy variously to the global norms brought about by REDD+, the customary resource practices of indigenous people, or to the state's laws. We show that the negotiations over forests in REDD+ reflect the influence of the specific historical and political-economic settings in which REDD+ activities take place, including pre-existing conflicts over forests and power relations underpinning forest management. From a policy perspective, our research suggests that any attempts to introduce simplified and uniform regulations for forest governance in REDD+ should be avoided, since local institutions and conceptions of justice will significantly influence what is regarded as legitimate policy and can thus be endorsed as inspiration for sustainable forest governance. Key policy insights REDD+ in Vietnam has spurred contestations over who is legitimately entitled to govern and manage forests. Claims and conflicts over forests can be explained by incompatible and distinct notions of justice, authority and identity. Contestations over justice pose radical challenges to any global and national efforts that attempt to implement simplified rules and ideas for forest based-climate change mitigation. Attention to justice, especially to compatibility and differences in ideas about justice, is crucial for sustainable forest governance.